Effectiveness of Exercise Interventions for Pediatric Incontinence: A Systematic Review - Ueki, Ngeduas (South East Asia Nursing Research, 2023)
Pediatric incontinence is a significant concern affecting children's physical, psychological, and social well-being. Exercise interventions, particularly pelvic floor muscle training (PFMT), have been proposed as effective treatments for managing this condition. This systematic review aims to evaluate the effectiveness of exercise interventions in treating pediatric incontinence. A comprehensive search was conducted across multiple databases, resulting in the inclusion of 12 studies that met the criteria. The results indicate that exercise interventions, especially PFMT, significantly reduce incontinence episodes and improve quality of life in children. However, further research is needed to establish standardized protocols and evaluate long-term outcomes.